Eventos hidroclimáticos extremos e vulnerabilidade socioambiental a inundações no Baixo-Açu – RN - Medeiros, Marysol Dantas de (2018)
The floods are linked to intense hydrometeorological phenomena, and are often aggravated by anthropic interventions on the environment. Generally, urban areas have more expressive numbers of people affected directly by the floods, however, the rural areas also show records of losses and losses resulting from this phenomenon. In the state of Rio Grande do Norte, the main cause for the occurrence of such flood events was derived from extreme hydrometeorological phenomena, mainly upstream of the Piranhas-Açu River. Thus, the main objective of the research is to analyze the socioenvironmental vulnerability of the municipalities that compose the Baixo-Açu Region in the state of Rio Grande do Norte, based on flood risks, correlating extreme rainfall events along the River Basin Piranhas-Açu and the maximum flows reached by the river. The elaboration of the Social Vulnerability Index (IVS) was based on the adaptation of the World Risk Report (2014), prepared by the United Nations, using data that denote social disadvantage. The estimation of the flood areas for the return periods of 5, 10, 50 and 100 years was performed using hydrodynamic modeling using HEC-RAS software. With the overlapping of the areas exposed to floods obtained in the hydrodynamic modeling and the social vulnerability of the municipalities of Baixo-Açu, it was possible to evaluate the Socio-Environmental Vulnerability to floods in the region. Thus, it was verified that the floods in the Baixo-Açu are provoked by consecutive days of rains, even if the one accumulated in 24 hours is relatively low. In the case of the Piranhas-Açu River, hydrodynamic modeling showed that even floods resulting from low recurrence times (5 and 10 years) floods flood large areas. In addition, it was found that high exposure made socio-environmental vulnerability increase considerably, even in municipalities with low and very low social vulnerability. It should be emphasized that the methodology of this research allows the insertion of several indicators in different scales, and can be applied to several vulnerability studies, whether on a global, regional or local scale.